Differential Expression of Chemokine Receptors and their Roles in Cancer Imaging - Nimmagadda, Sridhar (Frontiers in Oncology, 2012)
Chemokine/chemokine receptor interactions play diverse roles in cell migration and homeostasis. Emerging evidence suggests that cancer cells co-opt chemokine networks for survival, proliferation, immune evasion, and metastasis. Most of the chemokine receptors are reported to be involved in tumor progression. Given their extensive implication in cancer progression, several chemokine receptor/ligand axes are considered as potential therapeutic targets. This review provides a survey of chemokine receptor expression in cancer and evaluates the potential of chemokine receptor imaging as a tool for molecular characterization of cancer.